The stages of experimental work with formation of deontological culture of students in higher educational institutions and its analysis - Khliestova, Svitlana (ScienceRise: Pedagogical Education, 2017)
The article presents the results of experimental work on formation of deontological culture in students of higher educational institutions. The aim of research was the determination of effectiveness of introduction of structural-functional model into the practice of social-upbringing work of higher educational institution and provision of pedagogical conditions of formation of students’ deontological culture. For attaining this aim the theoretical-methodological analysis of the problem of formation of deontological culture in students of higher educational institutions was realized, the structural-functional model of formation of deontological culture in students of higher educational institutions was elaborated; the criteria, parameters and levels of formation of deontological culture in students of higher educational institutions were determined; the content-technological support of the process of formation of deontological culture in students of higher educational institutions was elaborated and introduced. The following methods of research were used: empirical ones – questionnaire, testing; narrative methods, independent expert assessment, analysis of pedagogical situations for determination of the level of formation of deontological culture in students; statistical ones – ranging, establishment of coefficient scale, qualitative and quantitative analysis of empirical data for verification of the results of experimental work as to the formation of deontological culture in students in social-upbringing work of higher educational institution